Ο Χρήστος Δημόπουλος στη Βιβλιοθήκη Καλαμπάκας clip (Kalambaka Library, 2017)
: Π So, π So, π So, π So, Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE